SOCIAL REFORM MOVEMENT FOR EMANCIPATION OF WOMEN IN 19TH AND 20TH CENTURY INDIA: A STUDY OF PANDITA RAMABAI - Wesley, Y (PEOPLE: International Journal of Social Sciences, 2017)
In recent times there has been a great interest in the history of women and gender relations in India. The rise of subaltern history has led to a renewed awareness of women’s role in history. Important women have played a very prominent role in the empowerment of women in India. Pandita Ramabai was one such woman. She was a pioneer in the field of women’s education and reform work for widows. The life and work of Pandita Ramabai (1858-1922) is immensely important today for understanding the social and religious reform movement in India. The research motivation was to study the mammoth contribution of strong women who have been relegated to the footnotes of history. The objective of this research is to glean details of the contribution of Pandita Ramabai in this regard. Another objective is to examine the magnitude of her work in the socio-religious milieu in which she operated. The methodology, which I have used, is both primary and secondary. I have referred to the books by eminent scholars and I have visited the Pandita Ramabai Mukti Mission at Kedgaon and had the privilege to access the works of Pandita Ramabai in the Archives of the Pandita Ramabai Mukti Mission. The findings of this paper reveal what a pioneer Pandita Ramabai was in the arena of women’s emancipation. The Research Outcome shows that Ramabai is a very important example of a woman’s voice, speaking fervently on the ways in which she saw men as having silenced and subdued Indian women